2015
DOI: 10.1017/s0007114515000744
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption of adults in Germany: results of the German National Nutrition Survey II based on diet history interviews

Abstract: The second German National Nutrition Survey (NVS II) aimed to evaluate food consumption and other aspects of nutritional behaviour of a representative sample of the German population, using a modular design with three different dietary assessment methods. To assess usual food consumption, 15 371 German speaking subjects 14–80 years of age completed a diet history interview between November 2005 and November 2006. With reference to the guidelines of the German Nutrition Society (DGE), NVS II observed that the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
135
4
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(163 citation statements)
references
References 18 publications
19
135
4
5
Order By: Relevance
“…The response rate was 42%. The study design is described in detail elsewhere [11]. Within the NVS II, food consumption was assessed using three dietary assessment methods: diet history interviews (n = 15.371), 24-h recalls (n = 13.926), and weighed food records (n = 975).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The response rate was 42%. The study design is described in detail elsewhere [11]. Within the NVS II, food consumption was assessed using three dietary assessment methods: diet history interviews (n = 15.371), 24-h recalls (n = 13.926), and weighed food records (n = 975).…”
Section: Methodsmentioning
confidence: 99%
“…To increase data quality, a plausibility check to identify and correct for input errors was conducted. Several times during the survey quality assurance checks were made by external supervisors [11].…”
Section: Diet History Interviewsmentioning
confidence: 99%
“…40 The German National Nutrition Survey II comprising 15 371 participants between the ages of 14 and 80 years reports a higher consumption of meat and meat products among men of all age groups as well as a higher intake of sweets, ice cream, sweeteners, soft drinks, and alcoholic beverages among men. 41 Women between the ages of 14 and 50 years reported a lower intake of milk, dairy products, and cheese. 41 Summarizing the abovementioned trials and nutrition surveys, it may be concluded that women of all age groups tend to opt for more healthy food.…”
Section: Sex and Gender Aspects Of Nutritionmentioning
confidence: 99%
“…41 Women between the ages of 14 and 50 years reported a lower intake of milk, dairy products, and cheese. 41 Summarizing the abovementioned trials and nutrition surveys, it may be concluded that women of all age groups tend to opt for more healthy food. Gender differences in eating behavior emerge during adolescence: girls aged 12 to 17 years give more attention to food choices than boys of the same age (62.5% vs 55.9%).…”
Section: Sex and Gender Aspects Of Nutritionmentioning
confidence: 99%
“…When calculating the weekly portions of eggs, the part of the egg which is used in food preparations (homemade egg pasta, sweets, biscuits, etc.) must be considered as well (Heuer et al, 2015;Memon et al, 2009;Maga, 1982).…”
Section: Introductionmentioning
confidence: 99%